2021
DOI: 10.3390/toxins13080588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Inner Exposure of Horses to Zearalenone (ZEN), Deoxynivalenol (DON) and Their Metabolites in Relation to Colic and Health-Related Clinical-Chemical Traits

Abstract: Mycotoxin contaminated feed has been associated with colic of horses caused by intestinal disorders. Whether such disease conditions alter the intestinal toxin metabolism and transfer across a compromised mucosal barrier is unknown. A screening approach was used to relate blood residue levels of DON, ZEN and their metabolites to the status of the horses (sick vs. healthy). A total of 55 clinically healthy horses from 6 different farms with varying feeding background served as control for sick horses (N = 102) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The lack of a control group was a significant limitation of the study. Previous studies identifying mycotoxin exposure of horses with colic and liver disease, also identified mycotoxins in control populations (Dänicke et al 2021;Durham 2022). Whilst we cannot conclude in this study if the increased liver enzyme concentrations were related to the mycotoxin exposure, it has demonstrated the frequency at which mycotoxins are identified in UK forage.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The lack of a control group was a significant limitation of the study. Previous studies identifying mycotoxin exposure of horses with colic and liver disease, also identified mycotoxins in control populations (Dänicke et al 2021;Durham 2022). Whilst we cannot conclude in this study if the increased liver enzyme concentrations were related to the mycotoxin exposure, it has demonstrated the frequency at which mycotoxins are identified in UK forage.…”
Section: Discussionmentioning
confidence: 94%
“…Feed refusal and gastrointestinal erosions have been noted in pigs after chronic exposure to deoxynivalenol (DON), which is a type of Type B trichothecenes (Pinton and Oswald, 2014). DON was found more commonly in colic cases compared to the control group in one study (Dänicke et al 2021). In a study by Raymon et.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation